PENGARUH PEMBERIAN REWARD DI MASA PANDEMI COVID19 TERHADAP MOTIVASI BELAJAR MATA PELAJARAN IPS SISWA KELAS VII SMP AL-WAFAA CABANGBUNGIN BEKASI (Jurnal Sosial Humaniora dan Pendidikan, 2022)
Teachers play an important role in the world of education. For this reason, as a teacher, you must have the principle of lifelong learning in order to find the best way to educate. The teacher plays a role in controlling the course of the learning process, which is expected to carry out the task as well as possible.The reward method is one way to motivate students to achieve achievements. This reward method is motivated by the concept of behavioristic theory, namely that learning is a change in behavior as a result of the interaction between stimulus and response (Ginanjar. 2013:2). Motivated students are initiated and motivated by a need. According to Abraham Maslow reward (award) is one of the basic needs that encourage a person to actualize himself (Wantah. 2005:164).Human needs consist of five levels from the lowest to the highest, starting from physiological needs, security, belonging and being loved, self-esteem, and self-actualization. If, a level of need has been met, then the need no longer functions as a motivator. This will then be able to strengthen the teacher regarding the appropriate response so that it can stimulate students. In addition to the basic needs factor, the student's family background also affects the strength of the response given by the student.